Water treadmill parameters needed to obtain land treadmill intensities in runners - Rife, R. K.; Myrer, J. W.; Vehrs, P.; Feland, J. B.; Hunter, I.; Fellingham, G. W. (Medicine & Science in Sports & Exercise, 2010)
Purpose: To establish water treadmill running parameters with shoes (WTR-S) and without water shoes (WTR-NS) needed to obtain known land treadmill running (LTR) cardiorespiratory responses.